The Relationship Between Good Corporate Governance Mechanisms, (Independent Commissioners, Managerial Ownerships, Foreign Ownership, Debt and Audit Quality) and The Performance of Shares in Conventional Banking Sector Companies Listed On The Indonesia Sto - Purwanti, Purwanti; Widiastuti, Widiastuti (Proceeding International Pelita Bangsa, 2023)
Good Corporate Governance is a company control system that can be seen from the relationship mechanism between the various parties who take care of.the company. The.bigger the company, the more problems and aspects that need.to be considered by management if they want to achieve maximum performance. This study aims to examine the influence of corporate. Governance mechanisms on company performance. The corporate governance mechanisms studied in the study include the board of commissioners, managerial ownership, foregin ownership, debt financing, audit quality and company stock performance. The sample of this study was 96 conventional banking companies registered inburse efek indonesia in the 2019-2022 period, the sampling method used in this study was purposive sampling. The results showed that the proportion of independent commissioners had no effect on stock performance. Managerialownership hasno influence on the performance ofthe stock. Foreign ownership has an influence on the performance of shares, the greater the foreign ownership. The quality of the audit has an influence on the performance of the stock. Debt has an influence on the performance of stocks. Independent commissioners, managerial and foreign ownership, audit quality and debt have a significant influence on the performance of stocks. This study used a tobin's Q.